Comparative analysis of all-terrain vehicles, motorcycle and automobile-related trauma in a rural border community of the USA. Issue 9 (27th October 2022) - Elzaim, Haissam S; Vatcheva, Kristina; Torres-Reveron, Annelyn; Pequeno, Gregery; Betancourt-Garcia, Monica M
Abstract : Introduction: There is widespread use of all-terrain vehicles (ATVs) in the USA for both work-related and recreational activities. In this study, we aimed to determine the difference in injury severity, Glasgow Coma scales and length of stay between ATV-related injuries and injuries sustained from motorcycles (MOTOs) and automobiles (AUTOs). Methods: We retrospectively analysed ATV, MOTO and AUTO injuries from a Level 2 Trauma Center between 01 January 2015 and 31 August 2020. Proportional odds regression analyses, as well as multivariable regression models, were used to analyse the data. Results: There were significantly more male and paediatric patients that suffered ATV-related injuries compared with MOTO or AUTO injuries. Victims of ATV-related injuries were also more likely to have open fractures. Paediatric patients were less likely to sustain an injury from either AUTO or MOTO accidents compared with ATV accidents. Patients with no drug use during injury and those who used protective equipment such as seat belts and child seats were significantly associated with lower Injury Severity Scores and higher Glasgow Coma Scale scores, indicating less severe injuries. Discussion: Paediatric patients are very likely to suffer sequela and long-term disability due to the severity of ATV-related injuries. Public awareness campaigns to educate our population, especially our youth, about the danger of ATV use are highly needed.